On sediment-induced problems under the dam rehabilitation and improvement project in India - Sanjay Giri (IAHR, 2020)
Dams and reservoirs are important assets in India with strong seasonal flow pattern variations and highly increasing water and energy demands due to rapid growth of economy and population.The negative impacts of dams and reservoirs can be attributed to poor planning, mismanagement, inefficient operations and insufficient consideration (or negligence) of mitigation strategies. The importance of dams and reservoirs and both their positive and negative impacts should be objectively measured vis-a-vis multi-sectorial benefits, specific priorities and demands.